Air pollution walk as an impact education tool for air quality sensitization: a pilot from an Indian megacity - D. Bej; S. S. Ghosh; S. Haldar; A. Roy (Geoscience Communication, 2024)
Air pollution has become a serious matter of concern in the global south, and a significant amount of funding has been used to create awareness of air pollution. The conventional method of sensitization relies on workshops where slide-based presentations, images, plots and graphs are shown to participants. However, sensitization about air quality using such an audio-visual format might not be sufficient to create adequate impact. Here, in this study, we propose a new sensitization technique, the pollution walk, where participants and a subject matter expert will walk through different urban micro-environments with a live air quality monitor. A pilot involving three such pollution walks with 24 participants was conducted in a South Asian megacity, and pre- and post-walk surveys were conducted. The results indicate a greater sense of understanding among the participants, and the multi-disciplinary nature of the air pollution problem has been communicated well. To understand the long-term impact, a survey after 1 year was conducted which clearly indicates high levels of awareness and behavioural changes among the participants.